Do Investors Value Sustainability? A Natural Experiment Examining Ranking and Fund Flows - HARTZMARK, SAMUEL M.; SUSSMAN, ABIGAIL B. (The Journal of finance (New York), 2019)
Examining a shock to the salience of the sustainability of the U.S. mutual fund market, we present causal evidence that investors marketwide value sustainability: being categorized as low sustainability resulted in net outflows of more than $12 billion while being categorized as high sustainability led to net inflows of more than $24 billion. Experimental evidence suggests that sustainability is viewed as positively predicting future performance, but we do not find evidence that high-sustainability funds outperform low-sustainability funds. The evidence is consistent with positive affect influencing expectations of sustainable fund performance and nonpecuniary motives influencing investment decisions.